2019
DOI: 10.21163/gt_2019.142.04
|View full text |Cite
|
Sign up to set email alerts
|

GMT Based Comparative Analysis and Geomorphological Mapping of the Kermadec and Tonga Trenches, Southwest Pacific Ocean

Abstract: Current study is focused on the GMT based modelling of the two hadal trenches located in southwest Pacific Ocean, eastwards from Australia: Tonga and Kermadec. Due to its inaccessible location, the seafloor of the deep-sea trench can only be visualized using remote sensing tools and advanced algorithms of data analysis. The importance of the developing and technical improving of the innovative methods in cartographic data processing is indisputable. Automatization in data analysis has been significantly increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…The GMT cross-section stacking methodology [51][52][53] proved to be a successful means of visualizing and plotting geomorphological models applied for the submarine bathymetry by effectively minimizing the hand-made cartographic routine. Using GMT enables to automatically digitize profiles, perform statistical analysis by plotting histograms and model trends for the general shape of the profiles using mathematical models of the lines approximation.…”
Section: Resultsmentioning
confidence: 99%
“…The GMT cross-section stacking methodology [51][52][53] proved to be a successful means of visualizing and plotting geomorphological models applied for the submarine bathymetry by effectively minimizing the hand-made cartographic routine. Using GMT enables to automatically digitize profiles, perform statistical analysis by plotting histograms and model trends for the general shape of the profiles using mathematical models of the lines approximation.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies reported methods, approaches and algorithm to better process and model data aimed at highlighting phenomena. Examples of various methods of statistical data analysis include data visualization, regressions, correlation, inference (Roberts et al, 2019;Lemenkova, 2019d), velocity modeling using grid based travel-time calculation method (Fujie et al, 2006), regression analysis of variables (Lemenkova, 2019c), factor analysis (Tucker, 1964;Lemenkova, 2018c), clustering and data grouping (Dumont et al, 2018;Lemenkova, 2019h). As for data instruments, examples of application include R programming language (Kotov & Pälike, 2017Lemenkova, 2018a), Python programming language (Yu et al, 2019;Lemenkova, 2019b), SPSS Statistics (Lemenkova, 2019e), Gretl (Lemenkova, 2019d).…”
Section: Discussionmentioning
confidence: 99%
“…Besides programming tools, analysis of the geological datasets can be performed by shell scripts as plugins embedded in GIS, or as scripting method of the geodata analysis and visualization using Generic Mapping Tools (GMT). Despite being a specifically cartographic toolset primarily designed for mapping, GMT also includes available modules for the statistical data analysis: histograms, plotting median and mean in a datasets [48][49][50][51][52][53][54][55].…”
Section: Discussionmentioning
confidence: 99%